Filosofi Penamaan Jenang dalam Budaya Jawa di Kabupaten Purworejo - Himmatul Ngaliyah (Asosiasi Periset Bahasa Sastra Indonesia, 2026)
Language is part of culture. Not everyone knows the philosophy and meaning behind the names of food. The purpose of this study is to find out the meaning, function, and value of the names of jenang in Purworejo Regency, Central Java. In addition, to find out what the philosophy of naming jenang is in Purworejo Regency, Central Java. From the perspective of semiotics (Roland Barthes' semiotic theory), semantics, culture and philosophy, several conclusions can be drawn. This research method includes a qualitative descriptive research method. Research data were obtained using the technique of listening and speaking. The data analysis method uses qualitative descriptive. Data analysis uses Rolland Barthes' semiotic theory. The author also briefly touches on meaning using a semantic perspective. In Purworejo Regency, eight (8) types of jenang are familiar in the daily lives of the people in Purworejo Regency, namely jenang sumsum, jenang abang putih, jenang procot, jenang candil, jenang katul, jenang pathi kerut (jenang garut), jenang krasikan, and jenang alot.